2013
DOI: 10.1209/0295-5075/103/67006
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport in magnetic fields by quantum spin liquid in the organic insulators EtMe 3 Sb[Pd(dmit) 2 ] 2 and κ -(BEDT - TTF) 2 Cu 2 (CN) 3

Abstract: -Measurements of the low-temperature thermal conductivity collected on insulators with geometrical frustration produce important experimental facts shedding light on the nature of quantum spin liquid composed of spinons. We employ a model of strongly correlated quantum spin liquid located near the fermion condensation phase transition to analyze the exciting measurements of the low-temperature thermal conductivity in magnetic fields collected on the organic insulators EtMe3Sb[Pd(dmit)2]2 and κ − (BEDT − TTF)2C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Second, as the system is away from the QCP, the number of spin states is rapidly decreased, and consequently the spin–lattice interaction is weakened. This is compatible with the SCQSL model 25 , where the QSL has much similarity with heavy-fermion liquids.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Second, as the system is away from the QCP, the number of spin states is rapidly decreased, and consequently the spin–lattice interaction is weakened. This is compatible with the SCQSL model 25 , where the QSL has much similarity with heavy-fermion liquids.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, κ is gradually increased by applying a magnetic field. A possible scenario is a model of a strongly correlated QSL (SCQSL) located near a fermion-condensation quantum-phase-transition point, where the QSL plays the role of heavy-fermion liquids placed into insulators 25 ; as a magnetic field is increased away from the QCP, the effective mass of spinons, m *, is reduced, leading to the increase of the spin thermal conductivity. In fact, we have recently determined the H – T phase diagram based on a scaling analysis of χ , where a QCP is present near the zero field (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is suggested that the observed B-dependence implies that some spin-gaplike excitations coupling to the magnetic field are also present at low temperatures [45,46]. As a result, we face a serious problem in interpretation of the experimental data in a consistent way, including the B-dependence of the heat conductivity [14]. Representing a special case of QSL, SCQSL is a quantum state of matter composed of spinons-chargeless fermionic particles with spin 1/2 [12,13,35].…”
Section: Spin-lattice Relaxation Rate Of Quantum Spin Liquidmentioning
confidence: 96%
“…Recently, a natural object, the herbertsmithite ZnCu 3 (OH) 6 Cl 2 has been exposed as a S = 1/2 kagome antiferromagnet [5]. New experimental investigations have revealed its unusual behavior [6][7][8][9][10] suggesting that herbertsmithite can be viewed as HF compound [11][12][13][14]. High-quality single crystals of ZnCu 3 (OH) 6 Cl 2 were synthesized and characterized [9].…”
Section: Thermodynamic Properties Of Quantum Spin Liquid In Insulatorsmentioning
confidence: 99%
“…( 6) [31]. TTF) 2 Cu 2 (CN) 3 [65,76,77]. Measurements of thermal transport are particularly salient in that they probe the low-lying elementary excitations of SCQSL in ZnCu 3 (OH) 6 Cl 2 and potentially reveal itinerant spin excitations that are mainly responsible for the heat transport.…”
Section: Relaxation and Transport Propertiesmentioning
confidence: 99%